1990
DOI: 10.1099/00207713-40-1-34
|View full text |Cite
|
Sign up to set email alerts
|

Saccharopolyspora spinosa sp. nov. Isolated from Soil Collected in a Sugar Mill Rum Still

Abstract: A new Saccharopolyspora species isolated from soil collected in a sugar mill rum still is described. This organism is characterized by pale yellowish pink aerial hyphae that bear long chains of spores encased in distinctive spiny spore sheaths. Fragmentation occurs when the organism is cultured in liquid media. The new species contains meso-diaminopimelic acid, arabinose, and galactose (cell wall chematype IV), has whole-cell sugar pattern type A, contains no mycolic acids, and contains phosphatidylcholine (ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
167
0
8

Year Published

1994
1994
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(175 citation statements)
references
References 17 publications
0
167
0
8
Order By: Relevance
“…S pinosad is a macrocyclic lactone derived from the fungus Saccharopolyspora spinosa (Mertz & Yao, 1990) The two most abundant components produced from fermentation of S. spinosa are spinosyns A and D (Fig. 1), which are the major active components of the flea product spinosad (Kirst et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…S pinosad is a macrocyclic lactone derived from the fungus Saccharopolyspora spinosa (Mertz & Yao, 1990) The two most abundant components produced from fermentation of S. spinosa are spinosyns A and D (Fig. 1), which are the major active components of the flea product spinosad (Kirst et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…S. spinosa ATCC 49460 (Mertz & Yao, 1990) was the host for some transformation and bacteriophage plaque-formation studies. S. spinosa PM89 is a novobiocin-treated derivative of ATCC 49460 lacking the plasmid pSASl (P. Matsushima & R. H. Baltz, unpublished).…”
Section: Methodsmentioning
confidence: 99%
“…Saccbaropolys-ora spinom was isolated from soil in a defunct sugar-mill rum still in the Virgin Islands (Mertz & Yao, 1990). S ' .…”
Section: Introductionmentioning
confidence: 99%
“…It can survive in the presence of 11% NaCl. 36) In our extraction experiment, the mycelium was ground into powder in liquid nitrogen to improve extraction efficiency. Previous studies have found that an accumulation of intracellular ectonie can help microbes to resist high osmotic pressure.…”
Section: Discussionmentioning
confidence: 99%